Sero-Prevalence of Anti HCV Among Blood Donors Attended at Transfusion Medicine Department of DMCH in 2013 - Karim, Shanaz; Hoque, Ehteshamul; Begum, Hussne Ara; Hoque, Mazharul (Anwer Khan Modern Medical College Journal, 2015)
Bacground: Post transfusion hepatitis through blood and blood product is still very high in our country. This present study was carried out to find out the prevalence of sero Positive of anti HCV among the blood donors attended at transfusion medicine department of DMCH in 2013 and also to prevent transmission of HCV infection through blood transfusion. Methodology: This cross sectional study was carried out at transfusion medicine department of DMCH from 1st January 2013 to 31st December 2013.Total blood donors were 27,560. Among total 31890 blood donors, relative donors were 25,773.and remaining 6,117 donors were voluntary donors. Blood donors of 18 - 60 years of both sexes were included in this study. Among 31,890 blood donors relative blood donors were 25,773(80.81%), voluntary blood donors were 6,117.(19.18%)Among 31,890 blood donors Anti HCV Sero positive were 33(0.1034%). Result: Among total blood donors male and female were 25,880 ( 81.15 % ) and 6010 (18.85 %) respectively. Age ranges of donors were 18 -40 years 28500 (86.23 % ) and 41 -60 years 3390 (10.63 %). Conclusion: Frequency of HCV seropositive among donors were 33 (.1034 %). Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 25-27